Back Cover: A Structured Monodisperse PEG for the Effective Suppression of Protein Aggregation (Angew. Chem. Int. Ed. 9/2013). Issue 9 (1st February 2013) - Muraoka, Takahiro; Adachi, Kota; Ui, Mihoko; Kawasaki, Shunichi; Sadhukhan, Nabanita; Obara, Haruki; Tochio, Hidehito; Shirakawa, Masahiro; Kinbara, Kazushi
<x xml:space="preserve">Abstract</x> Poly(ethylene glycol) (PEG) with a discrete triangular structure exhibits hydrophilicity/hydrophobicity switching at a lower temperature than the corresponding linear PEG. In their Communication on page 2430 ff, T. Muraoka, K. Kinbara, and co‐workers report that such a triangular PEG analogue helps lysozyme preserve the higher order structure at high temperatures and efficiently suppresses its thermal aggregation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>